Harmonization or Conflict? The Case of LGBT in the Interpretation of Islamic Law and Social Norms - Afrita, Juwika (Institut Manajemen Wiyata Indonesia, 2023)
Amidst the waves of globalization and social change, issues pertaining to sexual identity and gender orientation, particularly those involving Lesbian, Gay, Bisexual, and Transgender (LGBT) individuals, have given rise to complex discourses within the realms of religion and society. This article explores the emerging differences of opinion surrounding LGBT, notably in Indonesia, where the Indonesian Ulama Council (MUI) rejects LGBT as a sexual deviation contrary to the teachings of Islam, while the Liberal Islamic Network (JIL) acknowledges the diversity of human sexual preferences. Concurrently, in the Western context, the LGBT movement has spurred demands for political recognition, healthcare protection, and roles within military and parliamentary institutions. Additionally, this article highlights the role of social media in reshaping societal perceptions of LGBT and its impact on existing stigmas. Within this framework, the Islamic view towards LGBT is examined, depicting the conflict between religious perspectives and societal norms. Nonetheless, Islam also offers tolerance within the context of worship. This research employs a qualitative analysis approach to scrutinize Islamic legal interpretations and diverse societal perspectives on the LGBT issue. The aim is to investigate the harmony or conflict between the Islamic viewpoint on LGBT and prevailing societal norms. By delving deeply into the two primary pillars that shape individuals' perspectives and behaviors—namely Islamic legal interpretations and societal norms—this article seeks to provide a broader insight into the dynamics of LGBT-related debates. Through an inclusive and scientific approach, this article aspires to identify emerging points of harmony and conflict, thereby offering valuable contributions to discussions on pluralism, tolerance, and human rights within the context of religion and society.